2005
DOI: 10.1111/j.1523-1739.2005.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical Evidence of Widespread Chytrid Infection in North American Amphibian Populations

Abstract: Emerging infectious diseases may be contributing to the global decline of amphibian populations. In particular, chytridiomycosis, a cutaneous fungal infection of amphibians caused by the chytrid Batrachochytrium dendrobatidis, gained attention in the 1990s as an apparently new pathogen. This fungus has been implicated as the causative agent of widespread mortalities among wild amphibians in geographically disparate parts of the world. To investigate the global distribution, historical occurrence, and infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
191
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(208 citation statements)
references
References 49 publications
11
191
1
4
Order By: Relevance
“…A preserved R. pipiens from Colorado, 1974, represents the earliest known infection of that species (Carey et al, 1999), and recent studies found infected frogs in apparently healthy wild populations (Green et al, 2002). Historic evidence suggests that B. dendrobatidis is enzootic in R. pipiens (Ouellet et al, 2005). The strength of X. laevis resistance is consistent with a coevolutionary history with the fungus.…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 82%
See 2 more Smart Citations
“…A preserved R. pipiens from Colorado, 1974, represents the earliest known infection of that species (Carey et al, 1999), and recent studies found infected frogs in apparently healthy wild populations (Green et al, 2002). Historic evidence suggests that B. dendrobatidis is enzootic in R. pipiens (Ouellet et al, 2005). The strength of X. laevis resistance is consistent with a coevolutionary history with the fungus.…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 82%
“…Only two Panamanian species, C. prosoblepon and P. lemur, were predicted to be more resistant than North American R. pipiens, which survives infection with B. dendrobatidis (Ouellet et al, 2005). MALDI MS indicated that potentially novel antimicrobial peptides are present in the skin-peptide mixtures of C. prosoblepon.…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 99%
See 1 more Smart Citation
“…We build on existing reports of Bd thallus ultrastructure (Berger et al 1998, Davidson et al 2003, Ouellet et al 2005, Simoncelli et al. 2005, Une et al 2008) by providing TEM micrographs of Bd in bullfrogs and wood frogs and, to our knowledge, the first account of the host invasion process in any host species.…”
Section: Discussionmentioning
confidence: 99%
“…We build on existing reports of Bd thallus ultrastructure (Berger et al 1998, Davidson et al 2003, Ouellet et al 2005, Simoncelli et al 2005, Une et al 2008) by providing TEM micrographs of Bd in bullfrogs and wood frogs and, to our knowledge, the first account of the host invasion process in any host species. Host invasion by Bd parallels that in other exogenous chytrid fungi and ap pears morphologically similar in experimentally infected bullfrogs and wood frogs, species that display disparate levels of mortality risk for chytridiomycosis.…”
Section: Discussionmentioning
confidence: 99%